Women Contribution and Entrepreneurial Marketing to Family Welfare - Ma'mun Sarma (Economics Development Analysis Journal, 2019)
Home industry plays a strategic role to improve the family welfare and reduce poverty. Thus, this study aimed to analyze the influence of family characteristics, women contributions, entrepreneurial marketing, and government supports on the family welfare of home industry entrepreneurs. The study of entrepreneurial marketing in home industry that manage by women is the novelty of this study. To do so, it used a cross-sectional design, and Kendal Regency as the research site which was selected purposively. The sample was selected by convenience sampling technique and consisted of 67 women who had a home industry. Meanwhile the data were collected through interviews by using a questionnaire. Furthermore, the data were analyzed by using multiple regression analysis. The results revealed that the length of woman education showed a significantly positive influence on family welfare (B=62.868, 89; p=0,010). Additionally, the number of family members had a significantly negative influence (B=-220.633, 32; p=0,000) on family welfare. Meanwhile, woman age, women contribution, entrepreneurial marketing, and government supports had no significant influence on family welfare.